Pacientes com hepatite c da região oeste de minas gerais, Brasil: Satisfação com o atendimento odontológico oferecido pelo serviço especializado - Garbin, Cléa Adas Saliba [UNESP]; da Souza, Neila Paula [UNESP]; Garbin, Artênio José Ísper [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
Hepatitis C virus (HCV) infection is a worldwide health public problem, affecting over 123 million people. HCV infected individuals should have access to dental services, even those who are liver transplant candidates or who are undergoing medical treatment. It is also important that they are pleased with the service offered. Objective: Characterize the patients infected by HCV and verify their satisfaction with dental care in comparison to non infected individuals. Methods: A cross-sectional survey was carried out on 170 individuals, divided into two groups, HCV infected group (85 individuals) and non-infected group (85 individuals). Participants answered a questionnaire about their demographic data, risk factors, accessibility and satisfaction with dental service. Results: HCV infected group had lower education level, having only 30.6% finished pre-school. Considering sexual orientation, 70.6% of HCV infected group was heterosexual and 92.9% had one regular sexual partner. Sixty- five HCV infected individuals (77.4%) and 72 non-infected (85.7%) reported not using condoms during sexual intercourse. Forty-two percent of HCV infected group and 61.2% of non-infected group were satisfied with dental service. At multivariate analysis, education level was risk variable. Conclusion: Education level was a risk factor to HCV infection and HCV infected patients showed lower frequency of satisfaction with dental services.
Hepatitis C patients from west region of minas gerais State, Brazil: Satisfaction with dental care provided by specialized service
Keywords: Hepacivirus; Hepatitis C; Oral health; Personal satisfaction; Risk factors